Nexus between Public Expenditure and Economic Growth in Nepal (Economic Journal of Nepal, 2017)
The article attempts to identify the relationship between public expenditure and economic growth in Nepal. Public expenditure is a fundamental element for the economic growth. On employing, ARDL bound test on data set for the period of 1975-2016, it is found that there in a long-run relationship between the public expenditure and economic growth. The bound test and error correction term clearly specify that there exists a long run relationship between government expenditure and economic growth in Nepalese economy. From the empirical study, it is found that government expenditure has significant influence on real GDP, which is proxy for economic growth. The study confirms the Keynesian theory of making government expenditure to boost economic growth of Nepal.